A Case Report on a Rare Disease: Dyskeratosis Congenita - Shiferaw, Bethel (J Clin Med Res, 2015)
Dyskeratosis congenita (DC) is a rare hereditary disorder characterized by bone marrow failure, cancer predisposition (11-fold increase compared to general population), ectodermal dysplasia (nail dystrophy, oral leukoplakia, and abnormal skin pigmentation) and other additional somatic abnormalities. A 22-year-old man presented with fever, chills, and a painful throat. Leukoplakia was noted on his tongue and some of his fingers and toe nails were markedly dystrophic. His skin seemed spotted with pigmentation on the anterior chest and neck. Patient reported family history of “blood disease” and leukemia. He was admitted for the management of neutropenic fever (102.9 °F, WBC: 940, ANC: 404, platelets: 21,000 and Hb: 9.2), and was put on broad spectrum antibiotics. A bone marrow biopsy revealed normocellular marrow with erythroid predominance and mild dyserythropoiesis. Chromosomal analysis indicated no numerical or structural chromosomal abnormalities. The fluorescence in situ hybridization report did not reveal any assay specific abnormalities. Viral marker for hepatitis and studies of autoimmune antibodies showed negative results. CT scan had shown splenomegaly. Patient was discharged after he has been fever and symptoms free, with a follow-up at hematology clinic. Individuals with DC most commonly present with skin pigmentation, dystrophic nails and leukoplakia, as presented in this case. Genetic abnormality was not confirmed in our patient, but it is suggested that X-linked recessive pattern would be significant because of greater prevalence in men than in women (10:1). The distribution of blood counts and bone marrow biopsy categorizes our patient in the moderate aplastic anemia class which is the most prevalent pattern. When fever in young patients with a failing bone marrow is diagnosed, it is important that physicians rule out the possible underlying causes. DC is a rare disease, but can be diagnosed by simple inspection of the mucocutaneous abnormalities. DC is a severe multisystem disorder associated with premature morbidity and mortality. We believe that reporting this case would add more information to the existing fund of knowledge.